Properties of coatings based on fluorine-containing self-crosslinking latexes - Machotová, Jana; Černošková, Eva; Lucká, Barbora (University of Pardubice, 2018)
In this study, core-shell self-crosslinking latexes comprising different levels of copolymerized perfluorethyl groups in the shell layer of latex particles were prepared by the emulsion polymerization of 2,2,2-trifluoroethyl methacrylate, methyl methacrylate, butyl acrylate, and methacrylic acid as main monomers. The effect of crosslinking (inter-particle self-crosslinking and intra-particle crosslinking) was evaluated with the aim to spare the fluorinated monomer consumption while maintaining the desired water-resistant coating properties. For achieving the interparticle self-crosslinking, diacetone acrylamide was copolymerized into the shell layer of latex particles to provide sites for the subsequent reaction with adipic acid dihydrazide. The intra-particle crosslinking of latex particles was introduced by copolymerizing allylmethacrylate during the synthesis. The results showed that water sensitivity of coating films was reduced most notably by the level of crosslinking, while the effect of fluorine content in particle shell composition was minor only.
Keywords: latex; fluoropolymer; crosslinking; water-whitening; characterisation and properties